Who Needs Emotions? 2005
DOI: 10.1093/acprof:oso/9780195166194.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

The Architectural Basis of Affective States and Processes

Abstract: Much discussion of emotions and related topics is riddled with confusion because different authors use the key expressions with different meanings. Some confuse the concept of "emotion" with the more general concept of "affect", which covers other things besides emotions, including moods, attitudes, desires, preferences, intentions, dislikes, etc. Moreover researchers have different goals: some are concerned with understanding natural phenomena, while others are more concerned with producing useful artifacts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 36 publications
0
58
0
1
Order By: Relevance
“…E.g. the question whether a certain animal, or robot, has emotions or is conscious or feels pain suffers from the multiple confusions in our current notion(s) of mental states and processes (Sloman, 2002a(Sloman, , 2001aSloman et al, 2004). So, in part, our task is to explain how to make those obscure concepts clearer, for instance by interpreting them as 'architecture-based' concepts (op.cit).…”
Section: Non-physical Aspects Of Organisms and Their Environmentsmentioning
confidence: 99%
“…E.g. the question whether a certain animal, or robot, has emotions or is conscious or feels pain suffers from the multiple confusions in our current notion(s) of mental states and processes (Sloman, 2002a(Sloman, , 2001aSloman et al, 2004). So, in part, our task is to explain how to make those obscure concepts clearer, for instance by interpreting them as 'architecture-based' concepts (op.cit).…”
Section: Non-physical Aspects Of Organisms and Their Environmentsmentioning
confidence: 99%
“…The implementation of emotion dynamics is based on the assumption that an organisms natural, homeostatic state is characterized by emotional balance, which accompanies an agent's normal level of cognitive processing (Sloman, Chrisley & Scheutz 2005). Whenever an emotionally relevant internal or external stimulus is detected, however, its valence component serves as an emotional impulse, which disturbs the homeostasis causing certain levels of Pleasure and Arousal in the emotion module.…”
Section: Emotion Dynamics and Awareness Likelihoodmentioning
confidence: 99%
“…In this type of action-selection process, the system does not necessarily perform the same action every time for the same set of external stimuli. In ISAC's cognitive architecture, the Self Agent is responsible for metamanagement of its internal states similar to that proposed by Sloman [Sloman, et al, 2005] as shown in Figure 30. We have used the fixed, embedded emotion level as a part of the Self Agent in the experiment.…”
Section: Future Integrated Experimentsmentioning
confidence: 99%